2007
DOI: 10.1590/s0100-67622007000100001
|View full text |Cite
|
Sign up to set email alerts
|

Maturação de frutos de Caesalpinia echinata Lam., pau-brasil

Abstract: e Shoey Kanashiro 2 RESUMO -Estudaram-se parâmetros indicativos da maturação de frutos de árvores de Caesalpinia echinata, visando determinar a melhor época de colheita para propagação. Foram utilizadas 10 plantas-matriz cultivadas em Mogi-Guaçu, SP, nas quais foram etiquetadas 250 inflorescências no pico da floração para acompanhamento da maturação. As coletas de frutos tiveram início a partir da 5ª semana após a antese, prolongando-se até a 9ª, com intervalos de sete dias. Em cada coleta, analisaram-se os pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 6 publications
1
9
0
12
Order By: Relevance
“…Seed dry weight when combined with other features was a good indicator of physiological maturity for Torresia acreana (Firmino et al, 1996), for Dalbergia nigra (Martins and Silva, 1997), for Cedrela fissilis (Corvello et al, 1999), for Cnidosculus phyllacanthus for Mimosa caesalpiniifolia by Alves (2005), for Peltophorum dubium by Aquino et al (2006), for Machaerium brasiliense by Guimarães and Barbosa (2007), and for Caesalpinia echinata by Aguiar et al (2007). However, for Barbosa et al (1992) fruit and seed dry biomass of Copaifera langsdorffii were not good indicators of physiological maturity.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Seed dry weight when combined with other features was a good indicator of physiological maturity for Torresia acreana (Firmino et al, 1996), for Dalbergia nigra (Martins and Silva, 1997), for Cedrela fissilis (Corvello et al, 1999), for Cnidosculus phyllacanthus for Mimosa caesalpiniifolia by Alves (2005), for Peltophorum dubium by Aquino et al (2006), for Machaerium brasiliense by Guimarães and Barbosa (2007), and for Caesalpinia echinata by Aguiar et al (2007). However, for Barbosa et al (1992) fruit and seed dry biomass of Copaifera langsdorffii were not good indicators of physiological maturity.…”
Section: Resultsmentioning
confidence: 95%
“…Sena and Gariglio (1998) and Germaque et al (2002) reported that color change of fruits is a good indicator to assist in identifying the harvest stage of several species. The criterion of fruit color as an indicator of physiological seed quality was recommended to harvest seeds of Ricinus communis when fruits were brown colored (Silva et al, 2009) as well as for several species as reported by Aquino et al (2006) in Peltophorum dubium, for Machaerium brasiliense by Guimarães and Barbosa (2007), and by Aguiar et al, (2007) for Caesalpinia echinata, when fruits of these species were in transition from green to brown preceding the spontaneous opening.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of these parameters that characterize the physiological maturity of seeds was used in several species, such as pink-ipe (Gemaque;Davide;Faria, 2002), quaresmeira Dias;Pareira, 2005), thrush (Alves et al, 2005), red oak (Lopes and Soares, 2006), Brazil wood (Aguiar et al, 2007), Surinam cherry (Avila et al, 2009), canafístula (Nakagawa et al, 2010, Indian coral tree (Matheus;Corrêa, 2011), and Starburr (Duarte et al, 2012). ** Significant at 1% of probability by the F test.…”
Section: Grzybowski C R De S Et Almentioning
confidence: 99%
“…Physiological maturity of fruits is important for determination of the ideal period for harvest, processing, drying, storage and quality control of seeds (AGUIAR et al, 2007). Seed physiological maturity is when seeds reach maximum physiological quality, vigor, germination, size and dry matter weight.…”
Section: Introductionmentioning
confidence: 99%